2011
DOI: 10.1111/j.1745-6606.2011.01201.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impetus for (and Limited Power of) Business Self-Regulation: The Example of Advergames

Abstract: When people complain, government agencies often respond. When regulations are threatened, businesses often offer reassurances that the problems can be handled with a self‐regulation code. However, past analyses of the power of self‐regulation find that while companies' voluntary adherence to self‐defined guidelines may effect some change in the activities of some companies, the inherent limitations of self‐regulation in the United States may restrict its ability to actually halt or control the undesired practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 37 publications
1
47
0
2
Order By: Relevance
“…Twenty-eight studies collected data or obtained commercial monitoring data on food advertising, and used this information to assess advertising content, usually over time, to determine the success of actions (Adams et al, 2012;AFGC, 2012;ASC, 2010;Batada and Wootan, 2009;Brindal et al, 2011;Effertz and Wilcke, 2012;EU Pledge, 2010, 2011, 2012FTC, 2012;Hebden et al, 2011;Kim et al, 2012;King et al, 2011;Kolish and Hernandez, 2012;Kunkel et al, 2009;Ofcom, 2008Ofcom, , 2010Potvin Kent et al, 2011b;Powell et al, 2010;Quilliam et al, 2011;Rudd Center, 2010a, 2010b, 2011, 2012a, 2012bSpeers et al, 2011;Taras and Gage, 1995). The aim of these studies was to determine whether advertising content had changed as new actions were implemented.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-eight studies collected data or obtained commercial monitoring data on food advertising, and used this information to assess advertising content, usually over time, to determine the success of actions (Adams et al, 2012;AFGC, 2012;ASC, 2010;Batada and Wootan, 2009;Brindal et al, 2011;Effertz and Wilcke, 2012;EU Pledge, 2010, 2011, 2012FTC, 2012;Hebden et al, 2011;Kim et al, 2012;King et al, 2011;Kolish and Hernandez, 2012;Kunkel et al, 2009;Ofcom, 2008Ofcom, , 2010Potvin Kent et al, 2011b;Powell et al, 2010;Quilliam et al, 2011;Rudd Center, 2010a, 2010b, 2011, 2012a, 2012bSpeers et al, 2011;Taras and Gage, 1995). The aim of these studies was to determine whether advertising content had changed as new actions were implemented.…”
Section: Methodsmentioning
confidence: 99%
“…Actions included total bans on all advertising, bans on advertising of foods HFSS during specific hours, length of advertisements, and advertising of healthy food products, with the aim of reducing the volume of, and children's exposure to, advertising of foods HFSS, Body Mass Index, health costs, and improving diet. Twenty-five studies reported on the impact of self-regulation by industry (AFGC, 2012;ASC, 2010;Batada and Wootan, 2009;Brindal et al, 2011;Effertz and Wilcke, 2012;EU Pledge, 2010, 2011, 2012FTC, 2012;Hebden et al, 2011Kolish and Hernandez, 2012;Kunkel et al, 2009;Potvin Kent et al 2011a, 2011b, 2012Powell et al, 2010;Quilliam et al, 2011;Rudd Center, 2010a, 2010b, 2011, 2012a, 2012bSpeers et al, 2011). Actions included voluntary codes not to advertise foods HFSS during children's programming or directly to children under 12 years.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations